Modelo numérico de flujo bidimensional de la Bahía Paracas - Yzocupea, Víctor A. (2002)
The present study is an attempt to reproduce the hydrodynamic pattem of Paracas Bay. The bydrodynamic modeling allows us to understand how tbe circulation responds to the bathymetry, tides and wind system of the region. To acbieve tbis, a numerical model had to be conslructed. This model is based on a numerical approximation of the two-dimensional shallow water flow equations. These equations are tbe differential equations of motion in the X and Y direction and the differential equation of continuity. The dependen!variables are the vertica!ly averaged velocities U and V in the X and Y directions respectively, and the water levelll with respect to the mean sea leve!. The model has been tested with severa! theoretical tests and the results were very clase to tbe analytical solutions. After !bese tests, the model has been applied to Paracas Bay. First, the tidal tlow was modeled using historical tidal stage as the water leve!condition at the open boundary. Then, the wind-driven tlow was modeled using a non uniform wind distribution..© 2002 CSI. Al!rights reserved